Keberhasilan hidup parasitoid Diadegma semiclausum Hellen dan serangga inangnya Plutella xylostella (L.) terhadap aplikasi ekstrak biji srikaya (Annona squamosa L.) - Bonjok Istiaji; Djoko Prijono; Damayanti Buchori (Perhimpunan Entomologi Indonesia, 2018)
Control of Plutella xylostella L. can be done both biologically and chemically. Biological control is generally done by utilizing plant extracts to kill insect pests. This study aims to determine the effect of the extract of seeds on the mortality and development of parasitoid Diadegma semiclausum Hellen and its host, P. xylostella. The effect of Srikaya seed extract on P. xylostella larvae in the initial stage was tested by foliar rest method, while the residue method on the glass surface was used to test the effect of the extract of seed extract of Srikaya on the death of imago D. semiclausum. The effect of seed extract on parasitization and development of D. semiclausum was performed by exposing P. xylostella larvae contaminated by the extract of srikaya seeds in sublethal concentration (LC5 and LC10) in imago D. semiclausum. The results showed that extract of srikaya seeds at a concentration of 0.0632–0.1% at 24-hour contamination affected the death of the larva P. xylostella and the imago parasitoids D. semiclausum. Imago parasitoids are more susceptible to increased concentration of extracts than P. xylostella larvae. The developmental resistance of P. xylostella by Srikaya seed extract at concentrations used is generally unreal. Similarly, the barriers to the development of parasitoid D. semiclausum in hosts contaminated with sublethal concentrations (LC5 and LC10) of seed extract are generally not significantly different. The presence of Srikaya seed extract in the host also has no significant effect on the extent of parasitization, cocoon length, cocoon width, and cocoon weight. Therefore, there is a possibility to chemically and biologically integrate P. xylostella control.